Association between the frequency of daily intellectual activities and cognitive domains: A cross‐sectional study in older adults with complaints of forgetfulness. Issue 1 (3rd November 2020) - Iizuka, Ai; Suzuki, Hiroyuki; Ogawa, Susumu; Takahashi, Tomoya; Murayama, Sachiko; Kobayashi, Momoko; Fujiwara, Yoshinori
Abstract: Objectives: Frequent engagement in intellectual activities has been shown to reduce the risk of developing dementia. The present study sought to examine the association between the frequency of daily intellectual activities and cognitive domains in older adults with complaints of forgetfulness. Methods: A cross‐sectional study was conducted as a part of regional health examination in Tokyo from 2014 to 2016. A total of 436 participants were asked the frequency of intellectual activities in four categories: 1) reading, 2) writing, 3) using technology, and 4) watching TV and listening to the radio. The Japanese version of the Montreal Cognitive Assessment (MoCA‐J) scale was used for the cognitive assessments. The relationships between MoCA‐J scores and each intellectual activity were explored. Results: Binominal logistic regression analysis revealed that the frequencies of reading, writing, and using technology were significantly related to the language and attention, language, and memory domains, respectively, even after adjusting for demographic characteristics. Conclusions: The results suggested that the frequency of daily intellectual activities differed depending on the activity type, and each activity was related to a specific cognitive domain. Abstract : Frequent engagement in intellectual activities has been shown to maintain or improve cognitive function. The present study sought to examine the association between the frequency of daily intellectual activities and cognitive domains in older adults with complaints of forgetfulness. The results suggested that the frequencies of reading, writing, and using technology were significantly related to cognitive domains of the language and attention, language, and memory, respectively.